Effect of Heat Treatment on Ductility and Precipitation Size of Additively Manufactured AlSi10Mg - Sandra Megahed; Jannik Bühring; Tobias Duffe; Aleksandar Bach; Kai-Uwe Schröder; Johannes Henrich Schleifenbaum (Metals, 2022)
Laser powder bed fusion (LPBF) is a promising technology to manufacture complex components. Aluminium (Al) alloys are extensively implemented in automotive and aerospace applications for their exceptional strength and stiffness to weight ratios. AlSi10Mg is a precipitation strengthened alloy. Due to the high cooling rate during the LPBF process, a fine microstructure in as-built samples is expected, increasing strength and hardness values. However, the ductility of as-built AlSi10Mg alloys is limited. Heat treatment allows control of microstructure influencing the mechanical properties and ductility. In this study, AlSi10Mg samples with a relative density >99.5% were manufactured with LPBF. Surface roughness values of 10.86 µm were achieved. Tensile and three-point bending samples were printed for analysis. Since load conditions of lattice structures in compression are much more complex compared to that of volume samples, increasing tensile ductility is not sufficient to determine the suitability of lattice structures for applications where high deformations are required. Therefore, lattice structures for compression testing were manufactured and individually heat treated to achieve a ductility of at least 20%. The precipitation size was found to increase depending on heat treatment from 0.44 µm up to 2.25 µm, giving insight on deformation behavior.